Photoelectrochemical Study of Pyrargyrite in Acid Media. Issue 3 (9th January 2015) - Parajuli, Suman; Chhetri, Pushpa; Barakoti, Krishna K.; Stephenson, Wess Lee; Alpuche-Aviles, Mario A.
Abstract : Silver antimony sulfide (Ag3 SbS3, pyrargyrite) was synthesized by a solid state route from silver, antimony and sulfur powder precursors under an argon atmosphere. The product was characterized by powder X-ray diffraction (XRD) and found to be Ag3 SbS3 pyrargyrite alone, with a bandgap ( Eg ) of 2.0 eV. We analyzed the ground sample by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The bulk composition was found to be consistent with stoichiometric ratios. Surface characterization by X-ray photoelectron spectroscopy (XPS) indicates that the surface is depleted of Ag and S with an excess of Sb. Surface oxygen was found to be predominantly bound to Sb. The electrochemical and photoelectrochemical behavior of films on fluorine-doped tin oxide was compared to the behavior of bulk electrodes prepared from pieces of pyrargyrite grown under Ar. The films' photoelectrochemical behavior was consistent with a p-type material with the conduction band aligned to reduce H + in acid media. The photocurrent showed evidence of states with energies in the forbidden region that were localized at the surface and filled in the dark. Under illumination, photogenerated holes oxidized these surface states and caused recombination. On platinized films, electrons from H2 oxidation filled these states.